Implementasi Pembelajaran Batik Pada Masa Covid-19 di SMK N 8 Padang - Anggun Yodansi; Agusti Efi (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research is about the implementation of batik learning during the Covid-19 period at SMK N 8 Padang. During the Covid-19 pandemic, students learned from home without face to face, this resulted in the delay of the batik learning process, where students experienced difficulties in practicing batik. Because the learning process is carried out online and offline, while the batik learning process takes a long time. Students are only allowed 5 to 8 people in one day. So that the hours of face-to-face (practice) are only 3 to 4 times in one semester. This resulted in the delay in the batik learning process at SMK N 8 Padang during the Covid- 19 pandemic. This research method is a qualitative method. Types of data in the form of primary and secondary data. The informants of this research were Mr. Deswandi, Mrs. Rita and Mrs. Diana as batik learning teachers at SMK N 8 Padang. Data collection techniques through observation, interviews, and documentation. Data analysis techniques were carried out using interactive model analysis techniques related to the subject matter with data reduction, data collection, and conclusion drawing. The results of the study show that (1) the batik learning teacher prepares learning plans, namely learning tools such as syllabus, KI, KD, RPP, and modules for learning guides. (2) the process of implementing batik learning is carried out online through the zoom application and whatsapp group, starting with reading greetings and prayers, absent, motivation, giving material in the form of power points and learning videos, asking questions and giving assignments. (3) the scoring is done in stages, starting from the design, canting, coloring, quality, neatness. The process of giving grades is done offline, students collect assignments at school. Obstacles in learning batik at SMK N 8 Padang, among others, the difficulty of learning to practice batik done online and offline.